Review on Design for Medical Device - Naqibah, Azman; Nik Hisyamudin, Muhd Nor; Mohd Fahrul, Hassan; Saifulnizan, Jamian; Muhammad Hanif, Abd Rashid; Badrul, Omar; Siti Zarina, Mohd Muji; Fariza, Mohamad; Mohd Fauzi, Ahmad; Faiz, Mohd Turan; Elmi, Abu Bakar (EDP Sciences, 2017)
Medical devices are one of the uprising star in product development due to high demand among users. Developing safe, effective and usable design is indeed a challenging work which faced by designer nowadays. There are comparative methods in designing medical device to achieve desired outcome. Weather designing a “User-friendly”, “Safe to use” or “Eco-friendly” product requires an exclusive method. This review paper might illuminate some light to the designers and researchers who choose to integrate those aspect in their design work in healthcare sector. A review on current method used on user-friendly approach, ensuring safety, regulations on safety of medical device and suggested standards to ensure safety in less complicated way. Thus, there is no solid method or standard yet to establish on safety for medical device.